Elites and space in the towns of medieval Slavonia : the cases of Gradec/Zagreb and Varaždin - Karbić, Marija (Array, 2019)
The paper focuses on the leading layer in the urban societies of medieval Slavonia, seeking to answer the following questions: Who comprised the urban elite in Slavonian towns? What were their professions and what properties did they own? What was the significance of family relations for the formation of elites, and what other factors could help an individual to join their ranks? An important issue regarding the urban elites is the relationship between the elites and urban space; thus, the spatial development of Gradec and Varaždin are discussed in the second part of the paper.